An Invertebrate Burn Wound Model That Recapitulates the Hallmarks of Burn Trauma and Infection Seen in Mammalian Models - Maslova, Evgenia; Shi, Yejiao; Sjöberg, Folke; Azevedo, Helena S.; Wareham, David W.; McCarthy, Ronan R. (Frontiers in Microbiology, 2020)
The primary reason for skin graft failure and the mortality of burn wound patients, particularly those in Burn Intensive Care Centres, is bacterial infection. Several animal models exist to study burn wound pathogens. The most commonly used model is the mouse, which can be used to study virulence determinants and pathogenicity of a wide range of clinically relevant burn wound pathogens. However, animal models of burn wound pathogenicity are governed by strict ethical guidelines and hindered by high levels of animal suffering and the high level of training that is required to achieve consistent reproducible results. In this study, we describe for the first time an invertebrate model of burn trauma and concomitant wound infection. We demonstrate that this model recapitulates many of the hallmarks of burn trauma and wound infection seen in mammalian models and in human patients. We outline how this model can be used to discriminate between high and low pathogenicity strains of two of the most common burn wound colonisers Pseudomonas aeruginosa and Staphylococcus aureus, and multi-drug resistant Acinetobacter baumannii. This model is less ethically challenging than traditional vertebrate burn wound models and has the capacity to enable experiments such as high throughput screening of both anti-infective compounds and genetic mutant libraries.